Особливості професійної педагогічної освіти бельгії - Процько, Євгенія (Studies in Comparative Education, 2015)
Статтю присвячено порівнянню характерних рис, закладених у скаутський освітньо-виховний ідеал та ідеал демократичного лідера у США. На основі проведеного аналізу на матеріалі опитування 100 респондентів зроблено висновок про те, що якості демократичного лідера не є природженими, вони набуваються у процесі виховання і соціалізації. Підкреслено, що формування демократичного лідера залежить від освітньо-виховного середовища, набуття рис демократичного лідера починається не у процесі трудової діяльності і кар’єрного росту, а у періодах дитинства і юнацьких років. Доведено, що риси демократичного лідера формуються у процесі спільної діяльності в атмосфері відповідальності і довіри, а неполітичні неформальні організації є потужним інструментом формування якостей демократичного лідера у дітей та молоді шкільного віку. Целью современных евроинтеграционных процессов определяется создание интеллектуального, поликультурного сообщества с помощью стандартизованной демократической системы профессионального образования. В статье проанализировано систему педагогического образования Бельгии, поскольку эта страна может стать примером в организации и реформировании педагогической подготовки учителей на европейском пространстве. Автор также определяет особенности профессиональной подготовки специалистов образования, которые поднимают страну на высокий уровень организации образования. The aim of modern Euro integration process is the creation of intellectual and polycultural society with a help of standard democratic system of the vocational education. We pay attention to the system of vocational education in Belgium that is resulted in the fact the country is a pioneer in its modernization. The higher educational establishments guarantee the students the effective possibilities to obtain the pedagogical qualification and the level of competence that is satisfactory for the professional activity. In the article the system of teacher education of Belgium has been analyzed as the country can be an example for European teacher training organization. The author defines the peculiarities of vocational educator training which ascend the country on the highest level of the education organization. The structure of the vocational education in Belgium, its international orientation, the devolution to solving educational problems on the regional level, the effective academic programs and the strict standards in realization of the educational quality control all show the complete and functional vocational pedagogical sector which is available to train a competent specialist in the sphere of education according to the modern requirements of the European and world job market. The above mentioned academic programs are usually completed with interdisciplinary and competence approaches in the organization of educational process. It is also mentioned that the education of a qualified teacher in Belgium starts when a pupil studies in a primary school when he obtains the basic notions of communication, judgments and the basic knowledge. After graduating a student defines the educational direction he will obtain the necessary qualification (vocational schools, higher educational establishments of university and non-university level). The problem under research is quite new and we see a perspective in its further investigation.